Central vein sign and diffusion MRI differentiate microstructural features within white matter lesions of multiple sclerosis patients with comorbidities - Lapucci, Caterina; Tazza, Francesco; Rebella, Silvia; Boffa, Giacomo; Sbragia, Elvira; Bruschi, Nicolò; Mancuso, Elisabetta; Mavilio, Nicola; Signori, Alessio; Roccatagliata, Luca; Cellerino, Maria; Schiavi, Simona; et al. (Frontiers in Neurology, 2023)
The Central Vein Sign (CVS) has been suggested as a potential biomarker to improve diagnostic specificity in multiple sclerosis (MS). Despite the similar features shared by MS, migraine and Small Vessel Disease (SVD)-related white matter (WM) T2-weighted hyperintensities, ex-vivo studies demonstrated their heterogeneous histopathological substrates. The aims of this study were to investigate the impact of SVD and migraine on the global and subregional assessment of the CVS in a large cohort of MS patients and to apply the Spherical Mean Technique (SMT) diffusion model to evaluate whether perivenular and non-perivenular lesions show distinctive microstructural features. 120 MS patients stratified into 4 Age Groups performed 3T brain MRI. WM lesions were classified in “perivenular” and “non-perivenular” by visual inspection of FLAIR* images; mean values of SMT metrics (INTRA, EXTRATRANS, EXTRAMD) were extracted. Of the 5303 lesions selected for the CVS assessment, 68.7% were perivenular. Significant differences were found between perivenular and non-perivenular lesion volume in the whole brain (p<0.001) and between perivenular and non-perivenular lesion volume and number in all the four subregions (p<0.001 for all). The percentage of perivenular lesions decreased from youngest to oldest patients (79.7%-57.7%), with the deep/subcortical WM of oldest patients as the only subregion where the number of perivenular was lower than the number of non-perivenular lesions. Older age and migraine were independent predictors of a lower percentage of perivenular lesions (p<0.001 and p=0.013 respectively). Whole brain perivenular lesions showed higher EXTRAMD and EXTRATRANS and lower INTRA (p=0.001, p=0.001 and p=0.02 respectively). Similar findings were found in the deep/subcortical WM (p=0.001 for all). INTRA was lower in periventricular (p=0.001), EXTRAMD was higher in juxtacortical and infratentorial (p=0.01 and p=0.05 respectively) and EXTRATRANS was higher in infratentorial perivenular lesions (p=0.04). Age and migraine have a relevant impact in reducing the percentage of perivenular lesions, particularly in the deep/subcortical WM. SMT may differentiate perivenular lesions, characterized by higher inflammation, demyelination and fiber disruption, from non-perivenular lesions. The development of new non-perivenular lesions, especially in the deep/subcortical WM of older patients, should be considered a “red flag” for a different -other than MS- pathophysiology.